Promoting reciprocal conversations in children with autism using text‐message prompting. (17th August 2021) - Canestaro, Vida M.; Akers, Jessica S.; O'Guinn, Nicole
Abstract: Script training has been shown to be an effective intervention for enhancing conversation skills in individuals with autism spectrum disorder (ASD). One area to which additional research should be dedicated is the effectiveness of different script delivery modalities. In the current study, we evaluated the use of text‐message prompting via an Apple Watch ® to increase appropriate conversations for three children with ASD. Our results suggest that the text‐message prompting was effective in increasing initiations and responses for two participants. Although the results are less clear for the third participant, we did observe an increase in the total number of initiations and responses following the intervention.